2020
DOI: 10.1161/hypertensionaha.119.14507
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Sphingolipid De Novo Synthesis Controls Blood Pressure by Regulating Signal Transduction and NO via Ceramide

Abstract: Ceramides are sphingolipids that modulate a variety of cellular processes via 2 major mechanisms: functioning as second messengers and regulating membrane biophysical properties, particularly lipid rafts, important signaling platforms. Altered sphingolipid levels have been implicated in many cardiovascular diseases, including hypertension, atherosclerosis, and diabetes mellitus–related conditions; however, molecular mechanisms by which ceramides impact endothelial functions remain poorly understood. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 57 publications
6
56
0
Order By: Relevance
“…Recent studies have pointed out a potential involvement of de novo biosynthesis of sphingolipids in hypertension and vascular diseases [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have pointed out a potential involvement of de novo biosynthesis of sphingolipids in hypertension and vascular diseases [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although both hypertensive strains shared some defects in the expression of other genes involved in de novo sphingolipid synthesis, the reduction of SPTLCs clearly suggest a key role of this metabolic route in the pathogenesis of the cerebrovascular disease. In this context, recent evidence indicates that the endothelial de novo synthesis of sphingolipids regulates blood pressure and endothelial homeostasis [ 30 ], highlighting the critical role of de novo synthetized sphingolipids in vascular diseases. The current data may indicate that the de novo synthesis of sphingolipids could be perturbed in the SHRSP.…”
Section: Discussionmentioning
confidence: 99%
“…1). In a recent publication, ceramide production by vascular endothelial cells was linked to preserving endothelial functionality and control of blood pressure [18]. The findings in the above-cited work also suggest that a large proportion of the circulating ceramides are produced by endothelial cells.…”
mentioning
confidence: 89%
“…While these biomarkers and diagnostic indicators represent advances in identifying and diagnosing CVD, the distinction between long chain (i.e., C16-C18) and very long chain (i.e., C20-C24) ceramides, which are generated by distinct ceramide synthase isoforms (CerS1/5/6 vs. CerS2/4, respectively) hints at potential mechanistic involvement. However, though much circulating lipid in general arises from liver, a detailed study demonstrated that circulating ceramides but not SM are derived from the endothelium of blood vessels (145). Interestingly the endothelium is functionally impaired in CVDs and could thus contribute to the plasma sphingolipid profile reported in HF.…”
Section: Sphingolipids As Emerging Biomarkers In Assessing Cardiovascmentioning
confidence: 99%